2013
DOI: 10.5194/npg-20-771-2013
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges for pre-earthquake electromagnetic emissions: shedding light from micro-scale plastic flow, granular packings, phase transitions and self-affinity notion of fracture process

Abstract: Abstract. Are there credible electromagnetic (EM) potential earthquake (EQ) precursors? This a question debated in the scientific community and there may be legitimate reasons for the critical views. The negative view concerning the existence of EM potential precursors is enhanced by features that accompany their observation which are considered as paradox ones, namely, these signals: (i) are not observed at the time of EQs occurrence and during the aftershock period, (ii) are not accompanied by large precurso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 156 publications
0
19
1
Order By: Relevance
“…It is generally reported that there are considerable correlation between occurrence time of earthquakes and those of emission: the strength of electromagnetic emission increase before and/or after earthquake (e.g., [20,21] Fujinawa et al [46], Parrot et al [47]). Some reports suggest that MHz emission occur several weeks before and the VLF emission occurs only in the nucleation period [8,9,17] in contrary to the appearance of VLF type variation (C type) in this report. We do not have data to discuss the MHz event because of the detection frequency that is less than about 10 kHz.…”
Section: Radio Wave Emissioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is generally reported that there are considerable correlation between occurrence time of earthquakes and those of emission: the strength of electromagnetic emission increase before and/or after earthquake (e.g., [20,21] Fujinawa et al [46], Parrot et al [47]). Some reports suggest that MHz emission occur several weeks before and the VLF emission occurs only in the nucleation period [8,9,17] in contrary to the appearance of VLF type variation (C type) in this report. We do not have data to discuss the MHz event because of the detection frequency that is less than about 10 kHz.…”
Section: Radio Wave Emissioncontrasting
confidence: 99%
“…Detailed investigation on activity in terms of spatiotemporal distribution and focal mechanism of microcracks revealed physical process of rock fracture. The investigation extends to the seismoelectromagnetic phenomena (e.g., Hayakawa and Fujinawa [15], Hayakawa [16], and Eftaxias and Potirakis [17]).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…To characterize the mode of fracturing more precisely, electromagnetic emission (EME) should also be measured simultaneously. According to the previous works (Eftaxias and Potirakis, 2013;Mori et al, 2004Mori et al, , 2009Baddari and Frolov, 2011), there are two kinds of AE signals: (i) AE signals with simultaneous EME that correspond to the creation of new surfaces, and (ii) AE events without EME corresponding to frictional noise of existing surfaces. While the former is closer to real earthquake events, the current experimental condition probably corresponds to the latter.…”
Section: Discussionmentioning
confidence: 99%
“…No method of forecasting earthquakes by the commonly used seismic measurements (SM) has yet been found (Bormann, 2011). The development of an earthquake usually takes place in three stages (Eftaxias & Potirakis, 2013): nucleation, stick-slip and a final drastic slip movement. At the nucleation stage, under the increasing stress amplitude, there appear many tiny fractures in the area around the existing fault (known as the ‘heterogeneous environment’).…”
Section: Introductionmentioning
confidence: 99%